Implementation of the Pancasila Student Profile Strengthening Project (P5) in the Learning of Islamic Religious Education in Elementary Schools - Leny Marlina; Nyimas Atika; Zahratul Musfiroh; Sekar Pangestuti (BASICA, 2026)
The Pancasila Student Profile is an important part of the Independent Curriculum, shaping students' character through contextual, sustainable project activities. The implementation of this project should be studied specifically in Islamic Religious Education to examine the relationship between religious values and Pancasila values. This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project in Islamic Religious Education and to identify the outcomes and factors that influence it. The method used is qualitative with a phenomenological approach. Data sources in this study are the Principal, Teachers and Grade IV Students, Data collection techniques were carried out through interviews, observation, and documentation, while data analysis used the Miles, Huberman, and Saldana models and tested for validity through triangulation. The results of the study indicate that the implementation of the Pancasila Student Profile Strengthening Project has been carried out through the stages of mapping, determining themes, compiling modules, and designing assessments. The results of the implementation show the development of three main dimensions: religious abilities through memorization of hadiths, attitudes of mutual cooperation, and independence. Supporting factors include the principal's policies, the presence of a leading teacher, and adequate facilities, while inhibiting factors stem from parents' perceptions of feeling burdened by the project activities. It can be concluded that the implementation of the Pancasila Student Profile Strengthening Project in Islamic Religious Education can shape students' character, although there are still challenges in parental support for P5 tasks.